2016 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference (EIConRusNW) 2016
DOI: 10.1109/eiconrusnw.2016.7448169
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid modelling as a tool for analysis of information systems security

Abstract: Article presents a method of complex assessment of information system security based on a hybrid simulation in AnyLogic and describes the simulation model structure comprising a set of parameters to define the functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The study is conducted in accordance with ethical standards that guarantee confidentiality, informed consent of participants and protection of their data [25]. If necessary, an ethical consent is obtained from the relevant institutional audit council [26].…”
Section: Ethical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study is conducted in accordance with ethical standards that guarantee confidentiality, informed consent of participants and protection of their data [25]. If necessary, an ethical consent is obtained from the relevant institutional audit council [26].…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Merging IoT data with information systems modeling allows companies to process information about their business processes in real time. This makes it possible to better understand the technological cycles, identify weaknesses and improve the efficiency of the process [25]. It was found that the use of IoT data allowed organizations to improve processes, reduce cycle time and increase overall productivity.…”
Section: Process Optimizationmentioning
confidence: 99%
“…The research literature on ISP compliance indicates that a general problem exists among employees who do not comply with prescribed information security policies [4]. It is also known that employees can be the most significant security threat to company information when they participate in risky behaviors such as accidentally installing viruses on company computers or using specific programs without prior knowledge [5]. Finally, Miller and Gregory [6] assert that consideration should be given to human behavior when authoring organizational policy.…”
Section: B Information Security Policiesmentioning
confidence: 99%